Theory ofElasticity - Maceri, Aldo.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
The Theory of Elasticity moves freely within a unified mathematical framework that provides the analytical tools for calculating stresses and deformations in a strained elastic body. All the elastic problems can be exactly analyzed employing the classical Mathematical analysis, with only the exception of the unilateral problems for which it is mandatory to use the Functional analysis. This book focuses on the practical application of the theoretical results. It gives to engineers, in a simple form, a clear indication of the necessary fundamental knowledge of the Theory of elasticity. The author develops the subjects in a classical way, but in light of the modern Mathematical theory of the elasticity and with more accented relief to the connections with the Thermodynamics. To give a clear justification of the fundamental equations of thermoelasticity, he applies a technique of analysis proper of the Fluid dynamics. However in the discussion of the unilateral problems, where the Functional analysis is compulsory, he has related in detail the mathematical aspects of the theoretical analysis.
The Three-Dimensional Problem -- The Problem of Saint Venant -- The Two-Dimensional Problems -- The One-Dimensional Problems -- Thermoelasticity -- Stability -- Anisotropy -- Nonlinear Elasticity.
Keywords: Engineering; Materials; Engineering; Continuum Mechanics and Mechanics of Materials